DIDACTIC CONDITIONS FOR DEVELOPING PROSPECTIVE TEACHERS’ PEDAGOGICAL INTELLIGENCE - Kholbozorova Nasiba (Western European Studies, 2025)
This article explores how teacher-education programs can strengthen prospective teachers’ pedagogical intelligence—the ability to think reflectively, manage emotions, and make adaptive instructional decisions in real classrooms—by clarifying which didactic conditions most consistently support its development. A systematic literature review was conducted using PRISMA-style screening and thematic synthesis. Peer-reviewed studies published between 1980 and 2025 were searched in Scopus, Web of Science, ERIC (via ProQuest), PsycINFO, and Google Scholar, and 20 studies met the inclusion criteria. The synthesis identified five recurring conditions. First, social-emotional competence training supports well-being and classroom efficacy. Second, practice-based pedagogy helps candidates connect theory to core teaching practices and pedagogical reasoning. Third, structured feedback and mentoring strengthen self-regulated professional growth. Fourth, video-based learning develops professional vision by improving noticing, interpretation, and evidence-based discussion of classroom events. Finally, emerging work on AI highlights the need for ethical, humancentered judgment in technology-supported teaching. Taken together, the findings suggest that pedagogical intelligence grows most effectively when programs align coursework, practicum experiences, and guided reflection into a coherent developmental pathway. Future research should test integrated models longitudinally across diverse contexts and refine shared measures of pedagogical intelligence
Keywords: Pedagogical intelligence; pre-service teachers; didactic conditions